2008
DOI: 10.1111/j.1432-2277.2007.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of donation and quality of life in living kidney and liver donors

Abstract: Summary Italian guidelines on living donation demand that we ascertain the donor’s free and informed consent. Assessments to do so have to be conducted by an independent ‘third party’ who has nothing to do with the medical team treating the recipient. From February 2002 to December 2006, the Veneto Regional Authority’s Third Party Commission evaluated 201 living liver and kidney donors. A sample of these were contacted after their surgery to assess their living donation experience and quality of life (QoL); 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 31 publications
(36 reference statements)
8
45
0
1
Order By: Relevance
“…Most conducted examinations compare the HRQoL of LKD with gender-and/or age-matched healthy individuals. In fact, numerous studies report on equal or even better performance of LKD with regard to HRQoL [23,[27][28][29][30]. However, there are some reports about a negative impact on donor HRQoL [31,32].…”
Section: Introductionmentioning
confidence: 96%
“…Most conducted examinations compare the HRQoL of LKD with gender-and/or age-matched healthy individuals. In fact, numerous studies report on equal or even better performance of LKD with regard to HRQoL [23,[27][28][29][30]. However, there are some reports about a negative impact on donor HRQoL [31,32].…”
Section: Introductionmentioning
confidence: 96%
“…Reports suggest that the majority of living donors experience such levels of health-related quality of life (HRQOL) as similar to or exceeding that of the general population (26)(27)(28). Nevertheless, it has been consistently shown that select donors (<5%) experience significant psychological distress or retain highly negative attitudes about donation (29). In one study, potential donors who were overweight or obese, less educated, had prior psychiatric difficulties, were not white, or not first-degree relatives of the recipient represented groups at risk for poor HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence and anecdotes were presented that a small number of LDs develop persistent donation-related physical or psychosocial disabilities (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Therefore, there was advocacy for a limited-scope long-term follow-up of all donors to accurately determine rates of a small number of predefined endpoints and to provide a mechanism by which donors could self-report rare events.…”
Section: Quality Assurance Performance Improvement and Perioperativmentioning
confidence: 99%